Composite oxide solid solution, preparation method thereof and sodium ion battery

By using composite oxide solid solution as the negative electrode material in sodium ion batteries, the problem of poor volume expansion and cycle stability of existing materials during conversion and alloying reactions is solved, and electrochemical properties with high stability and high reversible capacity are achieved.

CN119905551APending Publication Date: 2025-04-29BEIJING ELECTRIC VEHICLE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411928708.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The existing sodium ion battery negative electrode materials have large volume expansion during conversion and alloying reactions, poor cycle stability, and are difficult to obtain practical application.

Method used

A composite oxide solid solution, including oxides of titanium oxide and non-titanium transition metal, is used to mix the solution of titanium salt sol with a non-titanium transition metal salt, hydrolysis reaction and hydrothermal reaction to form a solid solution, and heat treatment is carried out to form a replacement solid solution material.

Benefits of technology

This material combines the high stability of titanium oxide and the high reversible capacity of transition metal oxides such as iron oxide, copper oxide, nickel oxide, and cobalt oxide, which improves the performance of sodium ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119905551A_ABST
    Figure CN119905551A_ABST
Patent Text Reader

Abstract

The invention discloses a composite oxide solid solution, a preparation method thereof and a sodium ion battery. The composite oxide solid solution comprises titanium oxide and a non-titanium transition metal oxide, and in the composite oxide solid solution, the non-titanium transition metal oxide comprises one or more of iron oxide, copper oxide, nickel oxide and cobalt oxide. Therefore, transition metal element atoms such as iron, copper, nickel and cobalt are dissolved into crystal lattices of titanium oxide to form a composite oxide solid solution, and the material has high stability of a titanium oxide material and high reversible capacity of transition metal oxides such as iron oxide, copper oxide, nickel oxide and cobalt oxide, and is used as a negative electrode material of a sodium ion battery; the performance of the sodium-ion battery is favorably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of electrode materials, and in particular to a composite oxide solid solution and a preparation method thereof, and a sodium ion battery. Background Art

[0002] With the rapid development of automobile electrification and energy storage devices, lithium-ion batteries are widely used in the fields of 3C electronics and new energy vehicles due to their advantages such as high output voltage, long cycle life, low self-discharge rate, no memory and no pollution. However, as lithium resources are continuously consumed, lithium sources are becoming increasingly scarce. As a homologous element of lithium, the content of sodium in the earth's crust is about 300 times that of lithium. Sodium-ion batteries are expected to become a supplement to lithium-ion batteries due to their abundant raw material reserves, low cost and no pollution. In particular, they show great advantages in power station energy storage and are widely researched and developed.

[0003] The negative electrode is an important component of sodium-ion batteries, and plays an important role in the energy density and cycle life of sodium-ion batteries. The negative electrode materials for sodium-ion batteries currently under development include hard carbon, metal oxides, sulfides, silicon, tin, etc. Among them, the reversible capacity of hard carbon is about 300mAh / g, and the reversible capacity of metal oxides, silicon, tin and other materials is higher than that of hard carbon materials, and can even reach more than 1000mAh / g. However, due to the conversion and alloying reaction between metal oxides, silicon, tin and other materials and sodium, the volume expansion of such materials is large, the cycle stability is poor, and it is difficult to obtain practical applications. Titanium dioxide is a "zero strain" material with good cycle stability, but its specific capacity is low, and the theoretical specific capacity is only 150mAh / g.

[0004] Therefore, the current sodium-ion battery negative electrode materials and sodium-ion batteries still need to be improved. Summary of the invention

[0005] The present invention aims to alleviate or solve at least one of the above-mentioned problems to at least some extent.

[0006] In one aspect of the present invention, the present invention proposes a composite oxide solid solution. In some embodiments of the present invention, the composite oxide solid solution includes titanium oxide and an oxide of a non-titanium transition metal, and in the composite oxide solid solution, the oxide of the non-titanium transition metal includes one or more of iron oxide, copper oxide, nickel oxide, and cobalt oxide. Thus, transition metal element atoms such as iron, copper, nickel, and cobalt are dissolved into the lattice of titanium oxide to form a composite oxide solid solution. This material has both the high stability of titanium oxide materials and the high reversible capacity of transition metal oxides such as iron oxide, copper oxide, nickel oxide, and cobalt oxide. Using it as a negative electrode material for sodium ion batteries is beneficial to improving the performance of sodium ion batteries.

[0007] In some embodiments of the present invention, in the composite oxide solid solution, the molar ratio of titanium element to non-titanium transition metal element is 1: 1 to 5: 1. Thus, the titanium element and the non-titanium transition metal element have a suitable molar ratio, and the formed composite oxide solid solution has good stability and high reversible capacity.

[0008] In another aspect of the present invention, the present invention proposes a method for preparing a composite oxide solid solution. In some embodiments of the present invention, the preparation of the composite oxide solid solution includes: mixing a titanium salt sol with a solution of a non-titanium transition metal salt to obtain a first mixture, wherein the non-titanium transition metal salt includes one or more of an iron element, a copper element, a nickel element, and a cobalt element; adding a buffer to the first mixture to make the pH of the system 3 to 8, stirring, and hydrolyzing for 3 to 7 days to obtain a second mixture; placing the second mixture in a reaction vessel for a hydrothermal reaction, wherein the temperature of the hydrothermal reaction is 150°C to 220°C, and the time of the hydrothermal reaction is 10h to 20h; taking out the mixed solution of the hydrothermal reaction, filtering, washing, and drying to obtain a solid product; heat treating the solid product at a temperature of 350°C to 450°C to obtain a composite oxide solid solution. Thus, in the prepared composite oxide solid solution, atoms of transition metal elements such as iron, copper, nickel, and cobalt are dissolved in the lattice of titanium oxide to form a substitution solid solution material. The composite oxide solid solution has both the high stability of titanium oxide material and the high reversible capacity of transition metal oxides such as iron oxide, copper oxide, nickel oxide, and cobalt oxide. Using it as the negative electrode material of sodium ion batteries is beneficial to improving the performance of sodium ion batteries.

[0009] In some embodiments of the present invention, in the first mixture, the molar ratio of titanium element to non-titanium transition metal element is 1:1 to 5:1. This is conducive to forming a composite oxide solid solution with high stability and high reversible capacity.

[0010] In some embodiments of the present invention, the titanium salt sol is prepared by the following steps: dissolving the titanium salt in anhydrous ethanol, adding nitric acid solution dropwise under stirring, and adjusting the pH value of the mixture to 1-5 to obtain a titanium salt sol. Optionally, the titanium salt includes one or more of titanium trichloride, titanium tetrachloride, and tetrabutyl titanate.

[0011] In some embodiments of the present invention, the non-titanium transition metal salt includes one or more of iron nitrate, copper nitrate, nickel nitrate, and cobalt nitrate.

[0012] In some embodiments of the present invention, an aqueous solution of a non-titanium transition metal salt is mixed with anhydrous ethanol to obtain a solution of a non-titanium transition metal salt, and the solution of a non-titanium transition metal salt is added dropwise to the titanium salt sol to obtain the first mixture.

[0013] In some embodiments of the present invention, the buffer comprises at least one of hexamethylenetetramine and triethanolamine.

[0014] In some embodiments of the present invention, the heat treatment time is 0.5 h to 2 h, which is beneficial to improve the crystallinity of the product.

[0015] In another aspect of the present invention, the present invention proposes a sodium ion battery. In some embodiments of the present invention, the sodium ion battery includes a negative electrode plate, the negative electrode plate includes a negative electrode current collector and a negative electrode active material layer located on at least one surface of the negative electrode current collector, the negative electrode active material layer includes a negative electrode active material, and the negative electrode active material includes the composite oxide solid solution described above or the composite oxide solid solution prepared by the method described above. Thus, the sodium ion battery has all the characteristics and advantages of the composite oxide solid solution described above, which will not be repeated here. In general, the sodium ion battery has good stability and high capacity. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0017] Figure 1 shows the XRD spectrum of the composite oxide solid solution in Example 1 of the present invention;

[0018] Figure 2 The SEM image of the composite oxide solid solution in Example 1 of the present invention is shown;

[0019] Figure 3 The graph shows the relationship between the specific capacity and the number of cycles of the composite oxide solid solution in Example 1 of the present invention and the sample that has not been heat treated at 50 mA / g. DETAILED DESCRIPTION

[0020] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present invention, and cannot be understood as limiting the present invention.

[0021] In one aspect of the present invention, the present invention proposes a composite oxide solid solution. In some embodiments of the present invention, the composite oxide solid solution includes titanium oxide and an oxide of a non-titanium transition metal, and in the composite oxide solid solution, the oxide of the non-titanium transition metal includes one or more of iron oxide, copper oxide, nickel oxide, and cobalt oxide. Atoms of transition metal elements such as iron, copper, nickel, and cobalt are dissolved in the lattice of titanium oxide to form a substitution solid solution material. This material has both the high stability of titanium oxide and the high reversible capacity of transition metal oxides such as iron oxide, copper oxide, nickel oxide, and cobalt oxide. Using it as a negative electrode material for a sodium ion battery is beneficial to improving the performance of the sodium ion battery.

[0022] In some embodiments of the present invention, the composite oxide solid solution may include one of iron oxide, copper oxide, nickel oxide, and cobalt oxide. In some specific embodiments, the composite oxide solid solution may be composed of titanium oxide and iron oxide; in other specific embodiments, the composite oxide solid solution may be composed of titanium oxide and copper oxide; in other specific embodiments, the composite oxide solid solution may be composed of titanium oxide and nickel oxide; in other specific embodiments, the composite oxide solid solution may be composed of titanium oxide and cobalt oxide.

[0023] In some embodiments of the present invention, the composite oxide solid solution may include at least two of iron oxide, copper oxide, nickel oxide, and cobalt oxide, and at least two atoms of iron, copper, nickel, and cobalt are solid-dissolved in the lattice of titanium oxide to form a replacement solid solution material. In some specific embodiments, the composite oxide solid solution may be composed of titanium oxide, iron oxide, and copper oxide. In other specific embodiments, the composite oxide solid solution may be composed of titanium oxide, iron oxide, and nickel oxide. In other specific embodiments, the composite oxide solid solution may be composed of titanium oxide, nickel oxide, and cobalt oxide.

[0024] In some embodiments of the present invention, in the composite oxide solid solution, the molar ratio of titanium to non-titanium transition metal elements is 1:1 to 5:1. In some embodiments of the present invention, in the composite oxide solid solution, the molar ratio of titanium to non-titanium transition metal elements can be 1:1, 2:1, 3:1, 4:1, 5:1, etc. The molar ratio of titanium to non-titanium transition metal elements within the above range is conducive to improving the overall performance of the composite oxide solid solution, so that it has both the high stability of titanium oxide and the high reversible capacity of non-titanium transition metal oxides. It should be noted that when the composite oxide solid solution includes only one non-titanium transition metal oxide, the molar ratio of titanium to the first metal element (iron, copper, nickel or cobalt) is 1:1 to 5:1; when the composite oxide solid solution includes two or more non-titanium transition metal elements, the ratio of the molar number of titanium to the sum of the molar numbers of multiple non-titanium transition metal elements is 1:1 to 5:1.

[0025] In another aspect of the present invention, the present invention provides a method for preparing a composite oxide solid solution. In some embodiments of the present invention, the method for preparing a composite oxide solid solution may include the following steps:

[0026] S100: mixing the titanium salt sol with a solution of a non-titanium transition metal salt to obtain a first mixture.

[0027] In some embodiments of the present invention, the non-titanium transition metal salt may include one or more of iron, copper, nickel, and cobalt, and the non-titanium transition metal element may include one or more of iron, copper, nickel, and cobalt. The oxides of the above elements have a high reversible capacity, and the composite oxide solid solution is prepared using the above transition metal salt as a raw material, which is conducive to obtaining a negative electrode material with both high stability and high reversible capacity.

[0028] In some embodiments of the present invention, in the first mixture, the molar ratio of titanium element to non-titanium transition metal element may be 1:1 to 5:1, for example, the molar ratio of titanium element to non-titanium transition metal element may be 1:1, 2:1, 3:1, 4:1, 5:1, etc. The molar ratio of titanium element to non-titanium transition metal element within the above range is conducive to the solid solution of non-titanium transition metal element atoms into the lattice of titanium oxide to form a substitutional solid solution material.

[0029] In some embodiments of the present invention, the titanium salt sol is prepared by the following steps: dissolving the titanium salt in anhydrous ethanol, adding a nitric acid solution dropwise under stirring, and adjusting the pH value of the mixture to 1 to 5 to obtain the titanium salt sol. When the pH value is 1 to 5, it is more conducive to the dissolution of the titanium salt. Specifically, the pH value can be 1, 2, 3, 4 or 5. In some embodiments, the volume fraction of nitric acid in the nitric acid solution can be 2%.

[0030] In some embodiments, the titanium salt may include one or more of titanium trichloride, titanium tetrachloride, and tetrabutyl titanate, and the titanium salt may be subsequently hydrolyzed and hydrothermally reacted to form titanium oxide.

[0031] In some embodiments of the present invention, the non-titanium transition metal salt may include one or more of ferric nitrate, copper nitrate, nickel nitrate, and cobalt nitrate. In some embodiments of the present invention, the raw material of the non-titanium transition metal salt may use hydrated ferric nitrate, hydrated copper nitrate, hydrated nickel nitrate, hydrated cobalt nitrate, etc.

[0032] In some embodiments of the present invention, an aqueous solution of a non-titanium transition metal salt is first mixed with anhydrous ethanol to obtain a solution of a non-titanium transition metal salt, and then the solution of the non-titanium transition metal salt is slowly added dropwise to the titanium salt sol to obtain a first mixture.

[0033] S200: adding a buffer to the first mixture to adjust the pH of the system to 3-8, stirring, and hydrolyzing for 3-7 days to obtain a second mixture.

[0034] In some embodiments of the present invention, the buffer may include at least one of hexamethylenetetramine and triethanolamine. The above buffer may be used to adjust the pH value of the system so that the pH value of the system reaches a target range.

[0035] The pH of the system can be adjusted to 3, 4, 5, 6, 7, 8, etc. by adding a buffer to the first mixture. When the pH of the system is between 3 and 8, it is beneficial to the hydrolysis of the raw materials.

[0036] In some embodiments of the present invention, the hydrolysis reaction time can be 3 days, 4 days, 5 days, 6 days or 7 days. After 3 to 7 days of hydrolysis reaction, the titanium salt and non-titanium transition metal salt in the raw material can be hydrolyzed more fully, and then a solid solution is formed through a subsequent hydrothermal reaction.

[0037] S300: placing the second mixture in a reaction container to perform a hydrothermal reaction.

[0038] In some embodiments of the present invention, the reaction container may be a high-pressure reactor. The volume of the reaction container is not specifically limited in the present invention, and those skilled in the art may select it according to actual conditions.

[0039] In some embodiments of the present invention, the temperature of the hydrothermal reaction may be 150°C to 220°C, and the time of the hydrothermal reaction may be 10h to 20h. For example, the temperature of the hydrothermal reaction may be 150°C, 170°C, 190°C, 200°C, 220°C, etc., and the time of the hydrothermal reaction may be 10h, 12h, 15h, 18h, 20h, etc. At the above reaction temperature, the second mixture can react quickly to form a composite oxide solid solution; when the reaction time is within the above range, the second mixture can react more fully, and the utilization rate of the raw materials and the amount of the product can be improved.

[0040] S400: taking out the mixed solution of the hydrothermal reaction, filtering, washing and drying to obtain a solid product.

[0041] In some embodiments of the present invention, after the hydrothermal reaction is completed, the mixture in the reaction container is taken out, the precipitate is filtered out, and the precipitate is washed with deionized water and anhydrous ethanol respectively until the filtrate is neutral, and the precipitate is dried to obtain a solid product.

[0042] In some embodiments of the present invention, the precipitate can be dried at a temperature of 80° C. to 120° C. for 5 to 15 hours to obtain a dry solid product.

[0043] S500: heat-treating the solid product at a temperature of 350° C. to 450° C. to obtain a composite oxide solid solution.

[0044] In order to further improve the crystallinity and stability of the solid product obtained in S400, the solid product is heat treated, and the heat treatment temperature can be 350°C, 380°C, 400°C, 430°C, 450°C, etc.

[0045] In some embodiments of the present invention, the heat treatment time may be 0.5 h to 2 h, for example, the heat treatment time may be 0.5 h, 0.8 h, 1 h, 1.5 h, 2 h, etc. When the heat treatment time is within the above range, the crystallinity and stability of the solid product can be improved, and a shorter heat treatment time is beneficial to cost saving.

[0046] The composite oxide solid solution is prepared by the method proposed in the present invention, and the non-titanium transition metal element atoms can be dissolved into the lattice of titanium oxide to form a replacement solid solution material. The material has both the high stability of titanium oxide and the high reversible capacity of transition metal oxides such as iron oxide, copper oxide, nickel oxide, and cobalt oxide. It is used as the negative electrode material of sodium ion batteries, which is beneficial to improve the performance of sodium ion batteries. The method has a short hydrolysis process, uniform mixing of components, good particle dispersibility, short reaction time, and can also simplify the production process.

[0047] In another aspect of the present invention, the present invention proposes a sodium ion battery. In some embodiments of the present invention, the sodium ion battery may include a negative electrode plate, the negative electrode plate includes a negative electrode current collector and a negative electrode active material layer located on at least one surface of the negative electrode current collector, the negative electrode active material layer includes a negative electrode active material, and the negative electrode active material includes the composite oxide solid solution described above or a composite oxide solid solution prepared by the method described above. Thus, the sodium ion battery has all the characteristics and advantages of the composite oxide solid solution described above, which will not be repeated here. In general, the sodium ion battery has good cycle stability and high reversible capacity.

[0048] In some embodiments of the present invention, the negative electrode current collector of the sodium ion battery may be copper foil.

[0049] In some embodiments of the present invention, the negative electrode active material layer of the sodium ion battery may further include a binder (eg, PVDF) and a conductive agent (eg, Super P).

[0050] In some embodiments of the present invention, in the negative electrode active material layer, the mass ratio of the composite oxide solid solution, the binder and the conductive agent may be 8:1:1.

[0051] The sodium ion battery may further include a positive electrode plate, a separator and an electrolyte. The specific composition of the positive electrode plate, the separator and the electrolyte is not particularly limited in the present invention, and those skilled in the art may select and set them according to actual needs.

[0052] The sodium ion battery of the present invention can be used in electrical devices to supply power to the electrical devices.

[0053] In some embodiments of the present invention, the electrical device may be an electric car, an electric bicycle, an energy storage device, etc.

[0054] In other embodiments of the present invention, sodium ion batteries can also be used in energy storage devices.

[0055] The present invention will be described below by specific examples, and it will be appreciated by those skilled in the art that the following specific examples are only for illustrative purposes, and do not limit the scope of the present invention in any way. In addition, in the following examples, unless otherwise specified, the materials and equipment used are all commercially available. If in the following examples, specific processing conditions and processing methods are not clearly described, then conditions and methods known in the art can be used to process.

[0056] Example 1

[0057] Take 8mL of tetrabutyl titanate and dissolve it in 25mL of 2% nitric acid solution, stir for 1 hour until a uniform and transparent sol is formed. Mix 50mL (0.45mol / L) of ferric nitrate solution with 25mL of anhydrous ethanol, and then slowly drop it into the nitric acid sol of tetrabutyl titanate. Then weigh 3mL of triethanolamine and add it to the mixed sol to adjust the system pH to 3. Continue stirring and hydrolyze for 7 days.

[0058] The hydrolysis reaction product was added to a hydrothermal reactor, reacted at 180°C for 12 hours, and naturally cooled to room temperature. The mixed solution was taken out, the precipitate was filtered out, and washed with deionized water and anhydrous ethanol respectively until the filtrate was neutral. The precipitate was vacuum dried at 100°C for 12 hours to obtain a solid product. In order to further improve the crystallinity and stability of the material, the prepared solid product was heat treated at 400°C in an oxygen environment for 1 hour to obtain a heat-treated product.

[0059] refer to Figure 1 X-ray diffraction analysis shows that the product obtained after heat treatment in Example 1 exists in the form of pure TiO2·Fe2O3 solid solution. 4+ :Fe 3+ =1:1, and the molar ratio of titanium to iron in the product is 3:2. The SEM image of the product obtained after heat treatment in Example 1 can be referred to Figure 2It can be seen that the size of the prepared solid solution product is 30nm-80nm. The size of the product is at the nanoscale and has good reaction activity, indicating a high reversible capacity.

[0060] refer to Figure 3 ,in, Figure 3 Curve 1 and curve 2 are the relationship curves between the specific capacity and the number of cycles of the sodium ion battery prepared by using the solid product without heat treatment as the negative electrode material in Example 1 during the discharge process and the charge process, respectively. The negative electrode material has an initial reversible capacity of up to 620 mAh / g. After 30 cycles at a current density of 50 mA / g, the capacity can be maintained at 480 mAh / g. Figure 3 Curve 3 and curve 4 are the relationship curves between the specific capacity and the number of cycles of the sodium ion battery prepared by using the product after heat treatment in Example 1 as the negative electrode material during the discharge process and the charge process. The reversible capacity of the product after heat treatment in Example 1 reaches 600 mAh / g, and the capacity is maintained at 510 mAh / g after 30 cycles. The cycle stability is greatly improved compared with that before heat treatment. The reason is that the heat treatment further reduces the content of water of crystallization in the system and further improves the crystallinity of the material.

[0061] The performance test results of Example 1 and other examples and comparative examples are recorded in Table 1.

[0062] Example 2

[0063] Take 16mL of tetrabutyl titanate and dissolve it in 50mL of 2% nitric acid solution, and stir vigorously for 1h to form a uniform and transparent sol. Mix 50mL (0.45mol / L) of ferric nitrate sol with 25mL of anhydrous ethanol, and then slowly add it to the nitric acid sol of tetrabutyl titanate. Then weigh 3.5mL of triethanolamine and add it to the mixed sol, adjust the system pH to 3, and keep the other conditions the same as in Example 1, except that the hydrothermal temperature is 200℃ and the hydrothermal time is 15h. Among the raw materials, Ti 4 + :Fe 3+ =2:1.

[0064] In Examples 2 to 6, heat treatment was performed at the same temperature and time as in Example 1.

[0065] X-ray diffraction analysis shows that the obtained product exists in the form of pure TiO2·Fe2O3 solid solution. The electrochemical performance test results show that the composite oxide solid solution as a negative electrode material for sodium ion batteries has an initial reversible capacity of up to 487mAh / g; after 30 cycles at a current density of 50mA / g, the capacity can be maintained at 452mAh / g.

[0066] Example 3

[0067] Take 24mL of tetrabutyl titanate and dissolve it in 75mL of 2% nitric acid solution, and stir vigorously for 1h to form a uniform and transparent sol. Mix 50mL (0.45mol / L) of ferric nitrate sol with 25mL of anhydrous ethanol, and then slowly add it to the nitric acid sol of tetrabutyl titanate. Then weigh 4mL of triethanolamine and add it to the mixed sol, adjust the system pH to 3, and the other conditions are the same as in Example 1. In the raw materials, Ti 4+ :Fe 3+ =3:1.

[0068] X-ray diffraction analysis showed that the obtained product existed in the form of pure TiO2·Fe2O3 solid solution. The electrochemical performance test results showed that the composite oxide solid solution, as a negative electrode material for sodium ion batteries, had an initial reversible capacity of up to 372 mAh / g; after 30 cycles at a current density of 50 mA / g, the capacity could be maintained at 346 mAh / g.

[0069] Example 4

[0070] The preparation method is the same as that of Example 1, except that copper nitrate is used instead of iron nitrate in the reactants and the other conditions remain unchanged to obtain a Cu-Ti-O solid solution.

[0071] The results of electrochemical performance tests show that the composite oxide solid solution, as a negative electrode material for sodium ion batteries, has an initial reversible capacity of up to 462 mAh / g; after 30 cycles at a current density of 50 mA / g, the capacity can be maintained at 375 mAh / g.

[0072] Example 5

[0073] The preparation method is the same as that of Example 1, except that nickel nitrate is used instead of iron nitrate in the reactant and the other conditions remain unchanged to obtain a Ni-Ti-O solid solution.

[0074] The results of electrochemical performance tests show that the composite oxide solid solution, as a negative electrode material for sodium ion batteries, has an initial reversible capacity of up to 432 mAh / g; after 30 cycles at a current density of 50 mA / g, the capacity can be maintained at 374 mAh / g.

[0075] Example 6

[0076] The preparation method is the same as that of Example 5, except that cobalt nitrate is used in place of iron nitrate in the reactants and the other conditions remain unchanged to obtain a Co-Ti-O solid solution.

[0077] The results of electrochemical performance tests show that the composite oxide solid solution, as a negative electrode material for sodium ion batteries, has an initial reversible capacity of up to 532 mAh / g; after 30 cycles at a current density of 50 mA / g, the capacity can be maintained at 444 mAh / g.

[0078] Comparative Example 1

[0079] Use a measuring cylinder to measure 2mL of tetrabutyl titanate, pour it into the hydrothermal reactor, measure 20mL of distilled water at a volume ratio of 1:10, pour the distilled water into the hydrothermal reactor and mix it with tetrabutyl titanate, and then put the hydrothermal reactor into an oven. The reaction temperature is 150℃ and the reaction time is 10 hours. Cool naturally to room temperature, take out the mixed solution, filter out the precipitate, and wash it with deionized water and anhydrous ethanol respectively until the filtrate is neutral. Dry the precipitate in a vacuum at 80℃ for 12 hours to obtain the product.

[0080] X-ray diffraction analysis shows that the product obtained in Comparative Example 1 exists in the form of pure TiO2. During the charge and discharge process, the current density is 50mA / g, and the electrochemical performance test results show that the first reversible capacity of using crystalline TiO2 as the negative electrode material of the sodium ion battery is 165mAh / g, and after 30 cycles at a current density of 50mA / g, the capacity can be maintained at 152mAh / g.

[0081] Comparative Example 2

[0082] First, dissolve 0.005 mol of FeCl3·6H2O in 20 mL of deionized water to prepare a solution with a molar concentration of 0.25 mol / L. After stirring evenly, add 25% NH3·H2O until the pH of the solution is 8. Finally, transfer the prepared solution into a hydrothermal reactor. The reaction temperature is 200°C and the reaction time is 15 hours. Cool naturally to room temperature, take out the mixed solution, filter out the precipitate, wash with deionized water and anhydrous ethanol respectively until the filtrate is neutral, and use AgNO3 to detect the absence of Cl - The precipitate was dried under vacuum at 100°C for 12 hours to obtain the product.

[0083] X-ray diffraction analysis shows that the product obtained in Comparative Example 2 exists in the form of pure Fe2O3. During the charge and discharge process, the current density is 50mA / g, and the electrochemical performance test results show that the first reversible capacity of using crystalline Fe2O3 as the negative electrode material of the sodium ion battery is as high as 650mAh / g. After 30 cycles at a current density of 50mA / g, the capacity decays to 100mAh / g.

[0084] The electrochemical performance tests of all samples are as follows:

[0085] The ratio of active material (products in various embodiments and comparative examples), binder (PVDF) and conductive agent (Super P) is 8:1:1 (mass ratio), copper foil is used as the current collector, and the pole piece is a disc with a diameter of 10 mm. The working electrode is placed in a half-cell (CR2032 button battery) for testing, one pole is the test material electrode, and the other pole is the sodium sheet. The battery assembly is carried out in a glove box, and the water oxygen partial pressure in the glove box is controlled below 0.1ppm. In the electrolyte of the sodium ion battery, the solute is NaClO4, the concentration of NaClO4 is 1mol / L, and the solvent is EC / DEC (volume ratio 1:1). Using a blue electric tester, the voltage window range is 0.01-2.8V (vs Na + The test results are recorded in Table 1.

[0086] Table 1

[0087]

[0088] The method provided by the present invention is used to prepare a composite oxide solid solution, with a short hydrolysis process, uniform mixing of components, good particle dispersibility, shortened reaction time, and simplified production process. The prepared product is a transition metal ion-Ti-O solid solution material, which is different from the anatase structure of titanium oxide and pure transition metal oxide material, and belongs to a substitution type solid solution. When used as a negative electrode material for a sodium ion battery, it shows the characteristics of high structural stability of titanium oxide materials and high sodium storage capacity of transition metal oxide materials.

[0089] In general, transition metal-Ti-O solid solution is used as the negative electrode material of sodium ion battery, which has the advantages of high capacity, good cycle performance, low cost, etc. The material prepared by the method proposed in the present invention has the advantages of high structural stability and cycle stability of titanium oxide negative electrode and high capacity of transition metal oxide, overcoming the shortcomings of low capacity of the former and poor stability of the latter, so that the comprehensive electrochemical performance is improved, providing good prospects for practical application.

[0090] In the description of this specification, the description with reference to the terms "one embodiment", "another embodiment", "yet another embodiment", "some embodiments" and the like means that the specific features, structures, materials or characteristics described in conjunction with the embodiment are included in at least one embodiment of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in a suitable manner in any one or more embodiments or examples. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of different embodiments or examples, unless they are contradictory. In addition, it should be noted that in this specification, the terms "first" and "second" are used for descriptive purposes only and cannot be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated.

[0091] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A composite oxide solid solution, characterized in that: The composite oxide solid solution includes titanium oxide and an oxide of a non-titanium transition metal. In the composite oxide solid solution, the oxide of the non-titanium transition metal includes one or more of iron oxide, copper oxide, nickel oxide, and cobalt oxide.

2. The composite oxide solid solution according to claim 1, characterized in that In the composite oxide solid solution, the molar ratio of titanium element to non-titanium transition metal element is 1:1 to 5:

1.

3. A method for preparing a composite oxide solid solution, characterized in that: include: Mixing a titanium salt sol with a solution of a non-titanium transition metal salt to obtain a first mixture, wherein the non-titanium transition metal salt includes one or more of iron, copper, nickel, and cobalt; Adding a buffer to the first mixture to adjust the pH of the system to 3 to 8, stirring, and hydrolyzing for 3 to 7 days to obtain a second mixture; placing the second mixture in a reaction container and performing a hydrothermal reaction at a temperature of 150° C. to 220° C. for a time of 10 h to 20 h; The mixed solution of the hydrothermal reaction is taken out, filtered, washed and dried to obtain a solid product; The solid product is heat-treated at a temperature of 350° C. to 450° C. to obtain a composite oxide solid solution.

4. The method according to claim 3, characterized in that In the first mixture, the molar ratio of the titanium element to the non-titanium transition metal element is 1:1 to 5:

1.

5. The method according to claim 3 or 4, characterized in that: The titanium salt sol is prepared by the following steps: dissolving titanium salt in anhydrous ethanol, adding nitric acid solution dropwise under stirring, and adjusting the pH value of the mixture to 1-5 to obtain titanium salt sol. Optionally, the titanium salt includes one or more of titanium trichloride, titanium tetrachloride, and tetrabutyl titanate.

6. The method according to claim 3 or 4, characterized in that: The non-titanium transition metal salt includes one or more of iron nitrate, copper nitrate, nickel nitrate and cobalt nitrate.

7. The method according to claim 3 or 4, characterized in that: The aqueous solution of the non-titanium transition metal salt is mixed with anhydrous ethanol to obtain a solution of the non-titanium transition metal salt, and the solution of the non-titanium transition metal salt is added dropwise to the titanium salt sol to obtain the first mixture.

8. The method according to claim 3 or 4, characterized in that: The buffer comprises at least one of hexamethylenetetramine and triethanolamine.

9. The method according to claim 3 or 4, characterized in that: The heat treatment time is 0.5h to 2h.

10. A sodium ion battery, characterized in that: It includes a negative electrode plate, the negative electrode plate includes a negative electrode current collector and a negative electrode active material layer located on at least one surface of the negative electrode current collector, the negative electrode active material layer includes a negative electrode active material, and the negative electrode active material includes the composite oxide solid solution according to claim 1 or 2 or a composite oxide solid solution prepared by the method according to any one of claims 3 to 9.